Lunch in children and adolescents : meal pattern and relevance for the short-term cognitive functioning - Müller, Katrin; Justus Liebig University Giessen (My University, 2015)
Lunch is a meal that is eaten at midday and differs considerably between countries regarding meal type (cold vs. hot meal) and meal size (multicourse vs. snack meal). Considering the large number of schoolchildren attending all-day schools, information on their lunch pattern and on the acute effects of lunch on their cognitive functioning are of high public health relevance. Therefore, the objectives of this thesis were to describe and evaluate potential differences in lunchtime energy and food intake of adolescents (13-17 years) at their usual lunch location (school, home or elsewhere) and to examine the impact of skipping lunch vs. having lunch on schoolchildren s (12.6 ± 0.6 years) short-term cognitive functioning.To consider lunch pattern, the existing data of the HEalthy Lifestyle in Europe by Nutrition in Adolescence Cross-Sectional Study (HELENA-CSS) were used, in particular lunchtime food intake data obtained from two self-administered, computerized 24-hour recalls (24HR) and data on usual lunch location. Food intake was compared to lunch of the Optimized Mixed Diet (OMD), a meal-based dietary guideline for children and adolescents. Data on the acute effects of lunch on schoolchildren s cognitive functioning were collected in a randomised crossover study. Setting was an all-day school in Gelsenkirchen, Germany. Group 1 skipped lunch on study day 1 and received lunch ad libitum one week later on study day 2, while group 2 was treated vice versa. On both study days tonic alertness, visuospatial memory, and selective attention were tested in the early afternoon using a computerized test battery of the Vienna Test System (VTS).Even though the adolescents energy intake was comparable with the OMD, their food intake was suboptimal compared to the recommendation regardless of usual lunch location. Adolescents had more potatoes and less sweets at school, and more unsweetened drinks (water, coffee and tea) and vegetables at home when each compared with the other locations. Food intake of adolescents getting their lunch elsewhere was characterised by the smallest amounts of potatoes and the highest amounts of sweets. Except for tonic alertness there were no statistically significant differences in cognitive functioning between the skipping and the having lunch day. However, the higher number of omission errors on the skipping lunch day lost significance when adjusting for multiple testing.In conclusion, lunch on school days is improvable regardless of usual lunch location. To deduce and implement any cognition-related nutritional recommendations for schoolchildren, more research on the short-term effects of lunch on cognitive functioning is fundamental.

Als Mittagessen bezeichnet man eine in den Mittagsstunden eingenommene Mahlzeit. Art (kalte vs. warme Mahlzeit) und Größe (Mehr-Gänge-Menü vs. kleinere Zwischenmahlzeit) des Mittagessens können von Land zu Land sehr unterschiedlich ausfallen. In Anbetracht der Tatsache, dass eine beträchtliche Zahl an Schulkindern bis in den Nachmittag hinein in der Schule verbleibt, sind Kenntnisse zu deren mittäglichen Mahlzeitenmustern und zum Einfluss des Mittagessens auf deren kognitive Leistungsfähigkeit am frühen Nachmittag von hoher Public-Health-Relevanz.Ziele dieser Doktorarbeit waren deshalb, Unterschiede im Lebensmittelverzehr am Mittag bei Jugendlichen (13-17 Jahre) in Abhängigkeit vom Ort der gewöhnlichen Mahlzeiteneinnahme (Schule, zuhause, auswärts) zu beschreiben und zu bewerten und den akuten Effekt von Mittagessen vs. kein Mittagessen auf die kognitive Leistungsfähigkeit bei Schulkindern (12.6 ± 0.6 Jahre) zu untersuchen.Für die Betrachtung der mittäglichen Mahlzeitenmuster wurden vorhandene Daten der HELENA Studie genutzt, im Besonderen Daten zum Mittagessenverzehr aus zwei 24-Stunden-Recalls und Informationen zum Ort der gewöhnlichen Mahlzeiteneinnahme. Für die Bewertung wurden die lebensmittelbezogenen Empfehlungen für das Mittagessen der am Forschungsinstitut für Kinderernährung Dortmund entwickelten Optimierten Mischkost herangezogen. Die Daten zum Einfluss des Mittagessens auf die kognitive Leistungsfähigkeit am frühen Nachmittag wurden im Rahmen einer randomisierten Crossoverstudie erhoben, die in einer Gesamtschule in Gelsenkirchen durchgeführt wurde. Gruppe 1 erhielt an Testtag 1 kein Mittagessen und eine Woche später an Testtag 2 ein Mittagessen ad libitum. Mit Gruppe 2 wurde andersherum verfahren. Am frühen Nachmittag erfolgte jeweils die Erfassung der tonischen Alertness, des visuell-räumliches Gedächtnisses und der selektiven Aufmerksamkeit anhand einer computergestützten Testbatterie des Wiener Testsystems.Während die mittägliche Energiezufuhr der Jugendlichen den Empfehlungen der Optimierten Mischkost im Mittel entspricht, ist deren mittäglicher Lebensmittelverzehr unabhängig vom Ort der gewöhnlichen Mahlzeiteneinnahme nicht zufriedenstellend. In der Schule werden weniger Süßigkeiten und mehr Beilagen und zuhause mehr ungesüßte Getränke und Gemüse als jeweils an den anderen Orten verzehrt. Der Auswärtsverzehr ist durch die geringsten Mengen an Beilagen sowie die höchsten Mengen an Süßigkeiten gekennzeichnet. Außer der Nebenvariable Auslasser (tonische Alertness) war kein kognitiver Parameter signifikant mit dem Verzehr einer Mittagsmahlzeit assoziiert. Dieses Ergebnis war jedoch nach Adjustierung für multiples Testen nicht mehr signifikant.Schlussfolgernd lässt sich sagen, dass der Lebensmittelverzehr am Mittag bei Jugendlichen unabhängig vom Ort der gewöhnlichen Mahlzeiteneinnahme verbesserungswürdig ist. Um Empfehlungen zur Mittagsmahlzeit von Schulkindern unter Berücksichtigung des Einflusses auf die kognitive Leistungsfähigkeit abzuleiten und umzusetzen, ist weitere Forschung zum akuten Einfluss einer Mittagsmahlzeit auf die kognitive Leistungsfähigkeit grundlegend.
Mittagessen bei Kindern und Jugendlichen : Mahlzeitenmuster und Relevanz für die kurzfristige kognitive Leistungsfähigkeit
Keywords: Kinder; Mittagessen; kognitive Leistungsfähigkeit; Mahlzeitenmuster; children; lunch; cognition; meal pattern; ddc:640